2010
DOI: 10.1002/nau.20887
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial causes of irritating bladder symptoms in patients with sjögren's syndrome

Abstract: Various factors contribute to the irritating bladder symptoms in patients with SS, with DO being predominant. The LUTS developed in patients with SS are not due to any specific single etiology and that each patient must be individually carefully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…They observed that 87% of the patients had frequency, 66% nocturia and 52% urgency. Defining polyuria as total daily urine output more than 3,000 mL, they noted polyuria in four patients (17%) based upon the voiding diary; average voided volume was 294 mL [17]. However we observed no polyuria in our patients.…”
Section: Discussioncontrasting
confidence: 58%
“…They observed that 87% of the patients had frequency, 66% nocturia and 52% urgency. Defining polyuria as total daily urine output more than 3,000 mL, they noted polyuria in four patients (17%) based upon the voiding diary; average voided volume was 294 mL [17]. However we observed no polyuria in our patients.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, xerostomia, a cardinal symptom of pSS patients, may lead to excessive water intake, and consequently associated with OAB symptoms. [12]…”
Section: Discussionmentioning
confidence: 99%
“…5 Primary Sjo¨gren syndrome (pSS) patients are likely to present both with OAB symptoms (frequency, nocturia, urgency) and urodynamic abnormalities (such as detrusor overactivity) although further studies are needed to confirm these findings. 6 Case reports on this subject often reveal severe cases of bladder involvement requiring aggressive immunosuppressive treatment strategies. 7 Lupus cystitis has been described as a possible manifestation of systemic lupus erythematosus (SLE), and in a recent large, retrospective study it was strongly associated with lupus mesenteric vasculitis and poorer disease outcomes.…”
Section: Introductionmentioning
confidence: 99%